Perspektif Hexagon Fraud Theory Sebagai Indikator Kecurangan Laporan Keuangan - Widodo, Agus (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2023)
This study aims to examine fraudulent financial reporting as measured using the perspective of the hexagon fraud theory. Samples were taken based on purposive sampling criteria for companies in the LQ45 index category listed on the Indonesia Stock Exchange which published annual reports for 2019-2021. This research is an empirical research that is descriptive in nature and the analysis technique uses multiple linear regression. The results showed that the variable fraud hexagon: opportunity and razionalization had a significant negative effect on fraudulent financial reporting. While stimulus, capability, collusion and ego variables have no effect on fraudulent financial reporting